2006
DOI: 10.1055/s-2005-865871
|View full text |Cite
|
Sign up to set email alerts
|

Development and Prospective Evaluation of a Multimedia Teaching Course on Aortic Valve Replacement

Abstract: Our data demonstrate that multimedia driven training can adapt to the individual needs of learners and improves procedural knowledge required for open heart surgery. Consequently, the whole course forms part of the training of residents and students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…] Few studies to date have tested their effectiveness using stringent randomized controlled trials and those that do test animations with varied design that may not adhere to evidence-based principles of multimedia design [5,12]. To our knowledge, there have been no studies analyzing learning outcomes in relation to students' Kolb learning styles or that designed modules for medical students specifically using the aforementioned principles of multimedia design.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…] Few studies to date have tested their effectiveness using stringent randomized controlled trials and those that do test animations with varied design that may not adhere to evidence-based principles of multimedia design [5,12]. To our knowledge, there have been no studies analyzing learning outcomes in relation to students' Kolb learning styles or that designed modules for medical students specifically using the aforementioned principles of multimedia design.…”
Section: Discussionmentioning
confidence: 98%
“…This method of instruction is more effective than conventional chalk-on-blackboard lectures or static images presented in PowerPoint presentations in multiple areas of instruction [3] and may be an effective tool to combine multidisciplinary ideas [4] such as topics from the basic and clinical sciences. Of the e-learning tools available, animation is preferred by students [5,6]. Unfortunately, few studies have explored the effectiveness of animated modules in teaching medical students [7].…”
Section: Use Of Animated Modules In Medical Educationmentioning
confidence: 98%
“…Evidence in the literature proves that multimedia-driven learning has advantages in medical fields wherein an understanding of complex temporal and spatial events plays an important role [9]. Multimedia modules about aortic valve replacement have shown better educational value than print media with the same content for students studying heart surgery [10].…”
mentioning
confidence: 99%
“…Friedl et al has shown that multimedia learning ''can adapt to the individual needs of learners and improve procedural knowledge required for open heart surgery''. 3 Gold et al showed that online learning modules were used and appreciated by residents in thoracic surgery. 4 Vollmar et al showed that online continuing medical education can support learning and may establish a stimulus for translation of medical knowledge into daily clinical practice.…”
mentioning
confidence: 99%